WINGKAS POLITICAL MENTALITIES BEFORE THE 'INALIENABLE AGRARIAN COMMUNITY' AND THE MAPUCHE PEOPLE. (FROM IBÁÑEZ TO IBÁÑEZ, 1927- 1958) - Samaniego Mesías, Augusto (Revista de Historia Social y de las Mentalidades, 2011)
A core and distinctive aspect of the 20 th century policies toward the  Mapuche  people promoted by the majority society, including  political parties and the Chilean  State has been to protect the  inalienable nature of  indigenous agricultural communities .  We therefore make a distinction between two main trends. The first trend involves the  actions and logic of those who promoted turning ove r indigenous lands to the market,  thereby tailoring indigenous identities and rights  to meet the needs of homogenous  citizenship, state and laws; namely, the liberal id eological and political matrix of  “assimilation”. The second trend includes those who support the indivisibility of the  common land held by the indigenous  community , claiming it to be the historical  foundation of their ethnic-social identity and comm on indigenous rights.
Keywords: Mapuche communities; assimilationist p olicie; integrationist policies